Pembuatan Aplikasi Pencatatan Servis Mobil di PT. Armada International Motor Berbasis Android - Christine Dewi; Kumala Nindya Pramono (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2015)
PT. Armada Internasional Motor (PT. AIM) is anautomotive company that has not only a sales division but also aworkshop division. There are some problems that occur in theworkshop division of PT. AIM, namely the ineffectiveness of datarecording of new customers for new services, as they are usingdesktop-based application, hence, the customers must come tothe office beforehand. Furthermore, the data of service needsand the Letter of Reparation Order by the Checker are notdirectly known since they are in the desktop-system located inthe office, and the Service Advisor (SA) cannot directly find outwhether the service has been completed or not because theChecker has to make a manual report to SA. From some of thoseproblems, it is concluded that a data recording system with theportable and efficient mobile technology is highly needed. Theresult of this study is an application of car service data recordingfor both the SA and the Checker. The system of car service datarecording applies Google Cloud Messaging (GCM) technology tofacilitate the delivery of notice to the SA and the Checker.